The relationship of sodium dodecyl sedimentation test values to breadmaking quality of early generation dryland wheat lines - Oelofse, Rachel Mercia (University of the Free State, 2008)
Currently, high numbers of genotypes are unnecessarily being carried from generation to generation in the early generations of wheat breeding programs, only to be discarded in the advanced generations because of not reaching the strict quality standards. If a simple and reliable test could be used as an indication for baking quality in the early generations of the program, a more effective way to do culling of poor quality lines would be possible. Advanced (elite) and early generation material (F4) were evaluated to determine the influence of genotype and environment on the variation detected in SDS sedimentation. Firstly, nine intermediate hard red wheat elite lines and two intermediate hard red cultivars were evaluated for three consecutive years over eight locations in the Eastern Free State. Secondly, six F4 populations and two hard red cultivars were evaluated for one season at three locations in the Eastern Free State. Single plants in the F2 generation were selected by taking SDS sedimentation into consideration (selected group) and without taking SDS sedimentation into consideration (unselected group) and the influence of selection on the subsequent F4 generations was determined. The following conclusions were reached in the study: · There is a significant correlation between baking volume and SDS sedimentation. SDS sedimentation is therefore a reliable predictor of baking volume. · SDS sedimentation successfully discriminated between the genotypes in both the F4 and elite material. The contribution by genotype was high enough to make effective selection for SDS sedimentation possible. The large genotype x year effect on performance in contrast to the genotype x location effect in the elites, indicated that testing of genotypes across years may be more important than testing of genotypes across locations. · There were significant differences between the groups where selection was done on SDS sedimentation (selected) and groups where selection was done without taking SDS sedimentation into consideration (unselected groups) in most of the populations. The difference in SDS sedimentation between selected and unselected groups for most populations remained constant from the F2 to the F4 generation. Early generation SDS sedimentation selection would therefore effectively enhance baking quality in later generations. This would decrease the amount of lines that have to be evaluated in later generations and would have practical and financial advantages for a breeding program. · In both the elite and F4 material, there was a strong relationship between SDS sedimentation and dough strength, presumably because gluten responsible for the dough strength includes the glutenin, which takes part in the flocculation action of the SDS sedimentation process. SDS sedimentation selection in the early generations of a breeding program can therefore result in excessive dough strength in subsequent generations of certain crosses if a trait evaluating dough strength does not accompany SDS sedimentation selection. · The relationship between protein quantity (content) and SDS sedimentation varied, possibly due to difference in the glutenin quantity and quality between the genotypes. The negative correlation between SDS sedimentation and grain yield was highly significant. This could possibly be attributed to the influence of protein content, because it is well known that a negative association exists between protein content and grain yield, which was also evident in the study. · Mixing development time and hardness index (F4 generation) and grain yield and mixing development time (elite material) are the most definable independent variance predictors for SDS sedimentation in the F4 material. Therefore, mixing development time has a large influence on SDS sedimentation or is related to the same aspect, presumably gluten. · To perform effective SDS sedimentation selection in early generations, testing at one to two locations is adequate. A further increase of locations will result in a very small increase in precision, but would have large practical and financial implications and is therefore not recommended. The gains in precision obtained by increasing the number of years were substantially more than by increasing the number of replications. It is recommended that four to five years is essential for reliable SDS sedimentation selection. This can be done by selecting in the F2 to F5 generations in a breeding program, which will result in a decrease in variation and an improvement in SDS sedimentation stability. This will result in a drastic decrease in the effect of genotype x environmental interaction, which will make further selection later in the breeding program for SDS sedimentation selection unnecessary.

`n Groot aantal lyne word onnodig van generasie tot generasie oorgedra in die vroeë generasies van koringteeltprogramme, om later weer uitgeselekteer te word omdat dit te kort skiet aan die streng kwaliteitsvereistes vir vrystelling. `n Eenvoudige, betroubare parameter 164 wat `n goeie aanduiding van bakkwaliteit gee in die vroeë generasies van die teelprogram, sal effektiewe seleksie vroeg in die program moontlik maak. Gevorderde (elite) en vroeë-generasie (F4) materiaal is evalueer om te bepaal wat die invloed van omgewing en genotipe op die variasie in SDS sedimentasie is. Eerstens is nege intermediêre harde rooi elite lyne en twee intermediêre harde rooi kultivars geëvalueer vir drie opeenvolgende seisoene by agt lokaliteite in die Oos-Vrystaat. Tweedens is ses F4 populasies en twee harde rooi kultivars geëvalueer vir een seisoen by drie lokaliteite in die Oos-Vrystaat. Die invloed van F2 SDS sedimentasie seleksie op die F4 generasies is bepaal. In die F2 generasie se geselekteerde groep is enkelplante geselekteer met die hoogste SDS sedimentasie volume. In die ongeselekteerde groep is daar bloot op agronomiese voorkoms geselekteer, sonder om die SDS sedimentasie in ag te neem. Dievolgende gevolgtrekkings kan uit die studie gemaak word: • Daar is `n betekenisvolle korrelasie tussen bakvolume en SDS sedimentasie. SDS sedimentasie kan dus as `n betroubare aanduiding van bakvolume gebruik word. • SDS sedimentation het effektief tussen die genotipes in beide die F4 en elite materiaal diskrimineer. Die bydrae deur genotipe was hoog genoeg om effektiewe seleksie vir SDS sedimentasie moontlik te maak. Die groot bydra deur die genotipe x jaar interaksie dui aan dat evaluering van SDS sedimentasie oor jare meer belangrik is as evaluering oor lokaliteite. • Daar was betekenisvolle verskille tussen groepe waar vir die hoogste SDS sedimentasie geselekteer is (geselekteerde groep) en waar seleksie gedoen is bloot op agronomiese voorkoms, sonder om SDS sedimentasie in ag te neem (ongeselekteerde groep). Die verskil in SDS sedimentasie tussen die geselekteerde en ongeselekteerde groepe het konstant gebly van die F2 na die F4 generasie. Vroeë generasie seleksie vir SDS sedimentasie sal dus effektief selekteer vir hoër bakvolumes in latere generasies. Dit sal die hoeveelheid lyne wat in latere generasie geëvalueer moet word verminder, wat praktiese en finansiële voordele vir `n teelprogram inhou. • In beide die elite en F4 materiaal was die korrelasie tussen SDS sedimentasie en miksograaf mengtyd hoogs betekenisvol, moontlik omdat glutien glutenien bevat wat verantwoordelik is vir die flokkulering in die SDS sedimentasie proses en glutien ook verantwoordelik is vir deegsterkte. SDS sedimentasie seleksie in die vroeë generasies van `n teelprogram kan lei tot te sterk deeg mengeienskappe as dit nie gekombineer word met ‘n parameter wat deegsterkte ook evalueer nie. 165 • SDS sedimentasie en proteïeninhoud was hoogs betekenisvol in sommige gevalle, maar nie betekenisvol in ander, moontlik as gevolg van die verskille in die hoeveelheid en kwaliteit glutenien wat variëer het. Daar was `n negatiewe korrelasie tussen SDS sedimentasie en graanopbrengs in die elite materiaal. Dit kan moontlik toegeskryf word aan die invloed van proteïeninhoud, aangesien `n negatiewe korrelasie tussen graanopbrengs en proteïen-inhoud oor die algemeen bestaan, wat ook sigbaar was in die studie. • Miksograaf mengtyd en hardheid (F4 generasie) en graanopbrengs en miksograafmengtyd (elite generasie) is die eienskappe wat die meeste bydrae tot die variasie in SDS sedimentasie. Dit is dus duidelik dat miksograafmengtyd `n groot invloed op SDS sedimentasie het. • Een tot twee lokaliteite is voldoende om suksesvol vir SDS sedimentasie te selekteer in vroeë generasies. `n Verdere vermeerdering van die aantal lokaliteite sal slegs tot `n klein toename in proefakkuraatheid lei, maar groot praktiese en finansiële implikasies hê en word daarom nie aanbeveel nie. Die toename in proefakkuraatheid deur die aantal jare te vermeerder is baie groter as die toename in akkuraatheid met die vermeerdering van die aantal lokaliteite. • Evaluering vir vier tot vyf jaar is nodig vir betroubare evaluering van SDS sedimentasie. Dit kan gedoen word in die F2 tot F5 generasie van `n teelprogram, wat `n vermindering in die variasie en verbetering van stabiliteit vir SDS sedimentasie tot gevolg sal hê. Dit sal ook lei tot `n drastiese verlaging van die effek van genotipe x omgewings interaksie, wat verdere seleksie later in die program onnodig sal maak.
Thesis (Ph.D. (Plant Sciences (Plant Breeding))--University of the Free State, 2008
Keywords: Wheat -- Quality; Wheat -- Breeding; Sedimentation analysis; Wheat -- Analysis